Arabic, self and identity a study in conflict and displacement - Suleiman, Yasir (New York ; Oxford : Oxford University Press, 2011)
This book builds on Suleiman's earlier research on the link among the Arabic language, identity and conflict, which he explored at some length in 'The Arabic Language and National Identity' and 'A War of Words'. The present study builds on his interest in the symbolic realms of signification, and Suleiman approaches the Arabic language as a marker of identity and as a factor in sociopolitical conflict in society.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Anthropological linguistics -- Arab countries; Sociolinguistics -- Arab countries; Language and culture -- Arab countries; Ethnicity -- Arab countries